Molecular characterization of Hazaragie sheep native to Central Afghanistan - ASKAR MUSAVI, SAYED ALI; AHMAD, SOHAIL; IBRAHIM, MUHAMMAD (The Indian Journal of Animal Sciences, 2011)
Hazaragie is a small size, fat-tailed sheep breed found in the mountainous area of central Afghanistan. To characterize the breed on molecular level, DNA was extracted from blood samples of 44 animals randomly selected from their breeding tract, and each of 31 SSR markers was subjected to PCR using individual DNA sample, for amplification. Out of 31 SSR Markers 4 did not amplify, however, the remaining 27 were polymorphic giving total number of 170 alleles with average number of alleles 6.296 per locus, ranged from 3 (OarCP34) to 11 (BM1329). Mean effective number of alleles were 4.394 with allelic richness of 3.584 per locus. Higher heterozygosity (0.825) was observed in the population and hence expected heterozygosity (0.772), average heterozygosity (0.757) and gene diversity (0.772) were also higher. Inbreeding estimates within the population was calculated to be –0.069 on average across all loci. Most of the loci and overall population significantly deviate from Hardy Weinberg equilibrium. Polymorphism Information Content and Shannon information index was 0.534 and 1.581 respectively. Tests for Mutation drift equilibrium showed the absence of genetic bottleneck in the population. There was significant number of loci with heterozygosity excess under 2 of the 3 mutation models. Qualitative test utilizing allele frequencies showed the abundance of low frequency alleles and followed normal L-shape form on graph; represent the absence of genetic bottleneck in the population in recent past.